THE INFLUENCE OF CYBERLOAFING AND EMPLOYEE PRODUCTIVITY IN RSU. RATATOTOK BUYAT - Manuel, Angelia J.; Kindangen, Paulus; Saerang, Regina T. (FEB Universitas Sam Ratulangi Manado, 2019)
Abstract: Human resource becomes one of the important aspect in organization in order to be able to mobilize the rest of the resources. cyberloafing refers to the act of employees using their companie?s internet access for personal need during work hours. Cyberloafing term is an employee opportunity to reply personal emails, surf entertainment site, maintain a personal blog and even conduct personal business transactions while appearing to be absorbed with work-related tasks on the computer. This research aims to see the relationship between cyberloafing and employee productivity on RSU. Ratatotok Buyat. This research uses qualitative analysis method total sample are 15 employees. The result shows that, Cyberloafing does not significant on RSUP Ratatotok - Buyat productivity because all the employees are aware the right time how to using internet or mobile phone in while work. They were only using internet in free time or after work, it means there was no work for them. Based on employee answers, they were using internet for personal needs such as reading online news, chatting in social media like a Face book, and Instagram. RSU. Ratatotok Buyat should make grounded rules about using internet in while working and put CCTV to control employees while working. keywords:cyberloafing, employee performance